Diluted chemical bath deposition of CdZnS as prospective buffer layer in CIGS solar cell - Munna F.T.; Selvanathan V.; Sobayel K.; Muhammad G.; Asim N.; Amin N.; Sopian K.; Akhtaruzzaman M. (Elsevier Ltd, 2023)
Buffer layers; Cadmium sulfide; Deposition; II-VI semiconductors; Lime; Solar cells; Substrates; Thin films; Zinc sulfide; Chemical bath deposition technique; Chemical-bath deposition; Homogeneous distribution; Optical characterization; Optoelectronic properties; Precursor concentration; Soda lime glass substrate; X-ray diffractograms; Zinc compounds